Structure of the Systems of Orthogonal Projections Connected with Countable Coxeter Trees - Kirichenko, A. A.; Samoilenko, Yu. S.; Tymoshkevych, L. M. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
The paper is devoted to the investigation of representations of Temperley–Lieb-type algebras generated by orthogonal projections connected with countable Coxeter trees. The theorem on the structure of these systems of orthogonal projections is proved. Some examples are presented.